Abundance and Diversity of Dung Beetles (Coleoptera: Scarabaeoidea) as Affected by Grazing Management in the Nebraska Sandhills Ecosystem. Issue 1 (13th November 2020) - Wagner, Patrick M; Abagandura, Gandura Omar; Mamo, Martha; Weissling, Thomas; Wingeyer, Ana; Bradshaw, Jeffrey D
Abstract: Dung beetles (Coleoptera: Scarabaeoidea) serve a significant role in regulating ecosystem services on rangelands. However, the influence of grazing management on dung beetle communities remains largely unknown. The purpose of this study was to investigate dung beetle abundance and diversity throughout the grazing season in the Nebraska Sandhills Ecoregion. Grazing treatments included: continuous grazing (CONT), low-stocking rotational grazing (LSR), high-stocking rotational grazing (HSR), and no grazing (NG). The abundance and diversity of dung beetles were measured in the 2014 and 2015 grazing seasons using dung-baited pitfall traps. Dung beetle abundance for each grazing treatment was characterized through four indices: peak abundance, species richness, Simpson's diversity index, and Simpson's evenness. A total of 4, 192 dung beetles were collected through both years of trapping in this study. Peak abundance and species richness were greater in grazed treatments when compared to NG in both years. Peak abundance in the HSR was 200% (2014) and 120% (2015) higher than in the LSR. Species richness in the HSR was 70% (2014) and 61% (2015) higher than in the LSR, and 89% (2014) and 133% (2015) higher than in CONT. Simpson's diversity index was lower in the NG and CONT treatments when compared to the LSR or HSR treatments for both years. We conclude that rotational grazing, regardless of stocking density, promoted dung beetle abundance and diversity within the Nebraska Sandhills Ecoregion.